The words on the nature and purposes of man, life and all things - Nursi, Said 1873-1960 (From the Risale-i nur collection, 2008)
The Words is the first volume of the Risale-i Nur and consists of thirty-three independent parts or Words, which explain and prove aspects of the fundamental matters of belief. These consist of such matters as God s existence and unity, the manifestation of the Divine Names and attributes in creation, the resurrection of the dead and the hereafter, prophethood, the miraculousness of the Qur'an, the angels, the immortality of man s spirit, Divine Determining (fate or destiny), together with such questions as the true nature of man and the universe, and man s need to worship God. Each subject is explained with comparisons and allegories, and demonstrated with reasoned arguments and logical proofs. The most profound aspects of the truths of belief, which were formerly studied only by advanced scholars, are explained in such a way that everyone, even those to whom the subject is new, may understand without difficulty. This work answers brilliantly the attacks made on the Qur'an in the name of science and philosophy, and demonstrates the rationality of belief in God and logical absurdity of denial. It shows too that man s happiness and salvation both in this world and the next lie only in belief in God and knowledge of God. This new, revised edition includes a translation of Bediuzzaman's work in free verse, Lemeat (Gleams), which, though first published in 1921, is a sort of index of the Risale-i Nur.